Patterns of Self-Regulated Learning Strategies Employed by English Language Teachers in Five Selected Senior High Schools in North Lombok Regency - Untung Waluyo; Henny Soepriyanti; Udin; Thalia Qaulan Tsaqiila; Nurul Idiani (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research focuses on the patterns of self-regulated learning (SRL) strategies identified in English change agent teachers (guru penggerak) from five selected senior high schools in North Lombok Regency. Using a qualitative multiple-case study design, this research was conducted on ten English teachers which consist of five change agent teachers and 5 regular teachers who applied the Merdeka Curriculum learning activities. The study utilized in-depth interviews, classroom observations and document reviews for data collection. The data were analyzed thematically with triangulation to eliminate risk decision validity and credibility. Findings show that students’ preparedness falls into basic to intermediate level, with gradual enhancement (one step forward) for contextualized project-based tasks such as producing conversation video and acquaintance with tourists. The challenges to the implementation of Self-Regulated Learning (SRL), as identified in the study, include lack of resource, low student motivation and socio-cultural considerations. The study revealed that change agent teachers using SRL had enabled learners to take part in the classroom interaction enthusiastically. These findings are in line with the perspective of SRL supporting independent learning when teachers provide ongoing scaffolding, relevant project-based assignments and straightforward cycles of SRL